Process for directly regenerating failed lithium iron phosphate positive electrode material and application thereof
Through a simplified direct regeneration process, the failed lithium iron phosphate cathode material is regenerated, which solves the problems of lengthy and complex recycling processes and serious pollution in the prior art, and achieves high-efficiency and low-cost recycling and excellent performance of recycled materials.
Patent Information
- Application Number
- CN202411626006.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-14
AI Technical Summary
In the prior art, the recycling process of failed lithium iron phosphate batteries is lengthy and complex, and the use of a large number of chemicals causes contamination, making it difficult to be widely used.
A direct regeneration process is proposed, through steps such as soaking, calcining, mixed solution treatment and ball milling, the failed lithium iron phosphate positive electrode material is regenerated, simplifying the process and reducing pollution.
It has achieved efficient recycling of retired lithium iron phosphate batteries, reduced production costs, reduced pollution, excellent recycled materials performance, and is suitable for large-scale industrial applications.
Smart Images

Figure CN119481403A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waste power lithium battery recycling, and in particular to a process for directly regenerating failed lithium iron phosphate positive electrode materials and its application. Background Art
[0002] Since new energy vehicles were promoted in my country in 2013, the average service life of power batteries has been 5-8 years, and the first batch of power batteries put into the market in my country are basically facing retirement. At present, the first batch of new energy vehicle power batteries will be recycled in 2023, and the first recycling wave will come in the next few years. Recycling power batteries in a green, low-carbon and efficient way can not only increase the economic benefits of recycling related resources, but also reduce pollution to the environment, which is of great significance to the development of new energy in my country.
[0003] At present, the main process for recycling spent lithium iron phosphate batteries is through wet recycling: after the positive electrode is dissolved by strong acid, alkali is added to separate the lithium, iron ions and phosphate ions in the solution into precipitation. Since the process is lengthy and complicated, and the large amount of chemicals used will cause greenhouse gas, wastewater and other pollution, it is difficult to be widely used. Therefore, it is urgent to develop a direct regeneration process for spent lithium iron phosphate positive electrode materials with low consumption, less pollution, and the regenerated product can be directly used as a positive electrode material. Summary of the invention
[0004] In view of the defects in the prior art, the present invention proposes a process for directly regenerating failed lithium iron phosphate positive electrode materials and its application. The present invention can better recycle failed materials through direct regeneration, breaking through the limitations of traditional recycling processes.
[0005] In one aspect, the present invention provides a process for directly regenerating spent lithium iron phosphate cathode material, comprising the following steps:
[0006] S1. The spent lithium iron phosphate cathode material is immersed in deionized water and stirred, followed by filtration, and the filtrate is washed with an organic solvent and dried to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0007] S2. The spent lithium iron phosphate cathode material subjected to the preliminary treatment is calcined to obtain the spent lithium iron phosphate cathode material subjected to the secondary treatment, at which time the remaining PVDF and other impurities can be removed;
[0008] S3. The failed lithium iron phosphate cathode material powder after the secondary treatment is added to a mixed solution of deionized water and an alcohol solvent containing a lithium salt, stirred, filtered and then dried to obtain a failed lithium iron phosphate cathode material after the tertiary treatment;
[0009] S4. The spent lithium iron phosphate positive electrode material treated thrice is mixed with a carbon source material and ball-milled, and then calcined to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0010] The process of directly regenerating the spent lithium iron phosphate positive electrode material of the present invention can directly recycle the retired lithium iron phosphate batteries on the market. The process is short and easy to operate, which can greatly reduce pollution and save production costs. The regenerated lithium iron phosphate positive electrode material has excellent performance.
[0011] Furthermore, the lithium salt in step S3 is one or more of lithium acetylacetonate, lithium acetylacetate, and lithium iodide, preferably any one of lithium acetylacetonate and lithium acetylacetate. The lithium salt is dissolved in a water-alcohol mixed solution, and then lithium iron phosphate black powder is added to react with the black powder to adjust the near-surface structure, thereby effectively removing the degraded amorphous phase and residual fluorine compounds. The reconstructed surface promotes the relithiation process through direct lithium connection and reduced diffusion barriers, which is beneficial to quickly complete the lithium replenishment and repair process at high temperature.
[0012] Furthermore, the amount of carbon source material added in step S4 is 5%-16% of the mass of the failed lithium iron phosphate positive electrode material, such as 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, preferably 10%-13%, such as 10%, 11%, 12%, 13%.
[0013] Furthermore, the organic solvent in step S1 is one or more of ethanol, methanol, N-methylpyrrolidone, NN-dimethylformamide, and dimethyl sulfoxide.
[0014] Furthermore, in step S2, the calcination temperature is 250-450°C, such as 250°C, 300°C, 350°C, 400°C, 450°C, and the calcination time is 0.5-2h, such as 0.5h, 1h, 1.5h, 2h.
[0015] Furthermore, in step S4, the ball milling time is 0.5-5h, such as 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, and the ball milling speed is 50-220r / min, such as 50, 80, 100, 120, 150, 180, 200, 220r / min.
[0016] Furthermore, the carbon source material in step S4 is one or more of cellulose, sucrose, tannic acid, glucose, and vitamin C. The inventors have found that the cycle performance of lithium iron phosphate positive electrode materials can be significantly improved by reacting a lithium salt and water-alcohol mixed solution with lithium iron phosphate black powder and adding a carbon source for ball milling.
[0017] Furthermore, in step S4, the calcination temperature is 500-700°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, and the calcination time is 2-6h, such as 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h.
[0018] Furthermore, the concentration of the mixed solution containing lithium salt in step S3 is 3-10wt%.
[0019] Furthermore, the calcination in step S4 is performed under a specific atmosphere, such as any one of nitrogen, argon or argon-hydrogen mixed gas.
[0020] Furthermore, the drying in step S1 can be performed in a vacuum drying oven at a drying temperature of 50-80°C.
[0021] Furthermore, the drying in step S3 can be carried out in a vacuum drying oven at a drying temperature of 40-80° C. and a drying time of 5-8 hours.
[0022] Furthermore, in the mixed solution of deionized water and alcohol solvent in step S3, the volume ratio of the two is 1:(1-2), and adding lithium salt to the water-alcohol mixed solution can significantly improve the reaction efficiency with lithium iron phosphate black powder.
[0023] Furthermore, the stirring time in step S1 is 2-7 h, such as 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, and 6 h.
[0024] Furthermore, the stirring time in step S3 is 5-12 hours, and the stirring is performed at normal temperature and pressure.
[0025] Furthermore, the amount of the spent lithium iron phosphate positive electrode material powder added in the second treatment in step S3 is 0.001-10g.
[0026] Furthermore, the alcohol solvent is selected from any one or more of ethanol, methanol or propanol.
[0027] On the other hand, the present invention also provides the application of the direct regeneration process in treating waste power lithium-ion batteries.
[0028] Finally, the present invention also provides a lithium iron phosphate positive electrode material regenerated by the direct regeneration process.
[0029] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0030] (1) The performance of the lithium iron phosphate cathode material product regenerated by the direct regeneration process provided by the present invention is comparable to that of commercial lithium iron phosphate cathode materials;
[0031] (2) The direct regeneration process provided by the present invention is simple and suitable for large-scale industrial applications;
[0032] (3) The direct regeneration process provided by the present invention does not involve any reagents that may cause environmental pollution, and the regeneration process does not produce wastewater or waste residue, which is environmentally friendly and the entire process is green and efficient;
[0033] (4) The direct regeneration process provided by the present invention can perform coupled impurity removal at room temperature and pressure, reconstruct the lithium replenishment channel, and then directly regenerate the failed lithium iron phosphate efficiently at high temperature for a short time. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 1C charge-discharge curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 1;
[0036] Figure 2 This is a 1C long cycle curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 1;
[0037] Figure 3 1C charge-discharge curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 2;
[0038] Figure 4 This is a 1C long cycle curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 2;
[0039] Figure 5 1C charge-discharge curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 3;
[0040] Figure 6 This is a 1C long cycle curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 3;
[0041] Figure 7 1C charge-discharge curve of the lithium iron phosphate positive electrode material after final treatment obtained in Comparative Example 1;
[0042] Figure 8 This is a 1C long cycle curve of the lithium iron phosphate positive electrode material after final treatment obtained in Comparative Example 1. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0044] Example
[0045] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.
[0046] 1. The sources of raw materials for the embodiments and comparative examples are as follows:
[0047] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of the present invention are all commercially available, wherein the spent lithium iron phosphate positive electrode material was purchased from a battery disassembly manufacturer (Hebei Zhonghua Lithium Battery Technology Co., Ltd.).
[0048] 2. Various performance test methods
[0049] The regenerated lithium iron phosphate positive electrode material is prepared into positive electrode slurry in the mass ratio of regenerated lithium iron phosphate positive electrode material: conductive agent SP: binder PVDF: NMP = 80:10:10:100, coated on aluminum foil, and cut into electrode sheets after vacuum drying at 100°C for 12 hours. Subsequently, CR2032 button batteries are assembled in a glove box according to the button battery assembly process.
[0050] (1) Gram capacity performance test: tested by Xinwei battery testing system, the charging cut-off voltage is 4.3V, and the minimum discharge cut-off voltage is 2.5V.
[0051] (2) Long cycle stability test: The test is conducted using the Xinwei battery testing system with a rate set to 1C.
[0052] Example 1
[0053] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0054] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0055] S3. 8 mg (5% wt in the water-alcohol mixed solution) of lithium acetylacetonate was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60° C. for 6 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0056] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with glucose (the added amount was 7% wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 2 hours at a ball-milling speed of 160 rpm, and then calcined at 600°C for 6 hours in an argon atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0057] The battery charge and discharge curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 1 is as follows Figure 1 As shown, by comparing with the button cell assembled with the normal commercial lithium iron phosphate positive electrode material, it can be seen that the charge and discharge curve of the regenerated lithium iron phosphate positive electrode material in this embodiment is consistent with that of the normal commercial lithium iron phosphate positive electrode material, and the capacity and cycle performance are excellent, which meets the national standards of lithium iron phosphate batteries. The lithium iron phosphate positive electrode material regenerated by this method has good electrochemical properties, with a discharge capacity of 138mAh / g at 1C, and a capacity retention rate of 72.8% after 400 charge and discharge cycles, showing excellent rate performance, such as Figure 1 , Figure 2 shown.
[0058] Example 2
[0059] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0060] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0061] S3. 8 mg (5% wt in the water-alcohol mixed solution) of lithium acetylacetonate was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60° C. for 6 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0062] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with glucose (the added amount was 10% wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 2 hours at a ball-milling speed of 160 rpm, and then calcined at 600°C for 6 hours in an argon atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0063] The battery charge and discharge curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 2 is as follows Figure 3 As shown in the figure, by comparing with the button cell assembled with normal commercial lithium iron phosphate positive electrode material, it can be seen that the charge and discharge curve of the regenerated lithium iron phosphate positive electrode material in this embodiment is consistent with that of the normal commercial lithium iron phosphate positive electrode material, and the capacity and cycle performance are excellent, which meets the national standards for lithium iron phosphate batteries. The lithium iron phosphate material recycled by this method has good electrochemical properties, with a discharge capacity of 144mAh / g at 1C and a capacity retention rate of 92.4% after 400 charge and discharge cycles, showing excellent rate performance, such as Figure 3 , Figure 4 shown.
[0064] Example 3
[0065] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0066] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0067] S3. 8 mg (5% wt in the water-alcohol mixed solution) of lithium acetylacetonate was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60° C. for 6 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0068] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with glucose (the added amount was 15%wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 2 hours at a ball-milling speed of 160 rpm, and then calcined at 600°C for 6 hours in an argon atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0069] The battery charge and discharge curve of the regenerated lithium iron phosphate positive electrode material obtained in Example 3 is as follows Figure 5As shown, by comparing with the button cell assembled with the normal commercial lithium iron phosphate positive electrode material, it can be seen that the regenerated lithium iron phosphate positive electrode material of this embodiment is consistent with the charge and discharge curve of the normal commercial lithium iron phosphate positive electrode material, and the capacity and cycle performance are excellent, which meets the national standards of lithium iron phosphate batteries. The lithium iron phosphate material regenerated by this method has good electrochemical properties, with a discharge capacity of 133mAh / g at 1C, and a capacity retention rate of 85% after 400 charge and discharge cycles, showing excellent rate performance, such as Figure 5 , Figure 6 shown.
[0070] Example 4
[0071] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with N-methylpyrrolidone and dried in a vacuum drying oven at 50°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0072] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 250° C. for 2 h to obtain the failed lithium iron phosphate cathode material subjected to the secondary treatment;
[0073] S3. 16 mg (10% wt in the water-alcohol mixed solution) of lithium acetylacetonate was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 12 h, filtered and dried in a vacuum drying oven at 80° C. for 5 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0074] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with cellulose (the added amount was 5%wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 5 hours at a ball-milling speed of 220 rpm, and then calcined at 700°C for 3 hours in an argon atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0075] The regenerated lithium iron phosphate positive electrode material of this embodiment has excellent capacity and cycle performance, which meets the national standards for lithium iron phosphate batteries. The lithium iron phosphate material regenerated by this method has good electrochemical properties, with a discharge capacity of 135 mAh / g at 1C and a capacity retention rate of 70% after 400 charge and discharge cycles, showing excellent rate performance.
[0076] Example 5
[0077] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 3 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 70°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0078] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 450° C. for 1 h to obtain the failed lithium iron phosphate cathode material subjected to the secondary treatment;
[0079] S3. 4.8 mg (3% wt in the water-alcohol mixed solution) of lithium acetoacetate was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:2), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 5 h, filtered and dried in a vacuum drying oven at 40° C. for 8 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0080] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with glucose (the added amount was 16% wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 0.5 h at a ball-milling speed of 60 rpm, and then calcined at 500 °C for 6 h in a nitrogen atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0081] The regenerated lithium iron phosphate positive electrode material of this embodiment has excellent capacity and cycle performance, which meets the national standards for lithium iron phosphate batteries. The lithium iron phosphate material regenerated by this method has good electrochemical properties, with a discharge capacity of 140mAh / g at 1C and a capacity retention rate of 82% after 400 charge and discharge cycles, showing excellent rate performance.
[0082] Example 6
[0083] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0084] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0085] S3. 8 mg (5% wt in the water-alcohol mixed solution) of lithium acetoacetate was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60° C. for 6 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0086] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with glucose (the added amount was 10% wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 2 hours at a ball-milling speed of 160 rpm, and then calcined at 600°C for 6 hours in an argon atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0087] The regenerated lithium iron phosphate positive electrode material of this embodiment has excellent capacity and cycle performance, which meets the national standards for lithium iron phosphate batteries. The lithium iron phosphate material regenerated by this method has good electrochemical properties, with a discharge capacity of 141 mAh / g at 1C and a capacity retention rate of 90% after 400 charge and discharge cycles, showing excellent rate performance.
[0088] Example 7
[0089] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0090] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0091] S3. 8 mg (5% wt in the water-alcohol mixed solution) of lithium iodide was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60° C. for 6 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0092] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with glucose (the added amount was 10% wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 2 hours at a ball-milling speed of 160 rpm, and then calcined at 600°C for 6 hours in an argon atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0093] The regenerated lithium iron phosphate positive electrode material of this embodiment has excellent capacity and cycle performance, which meets the national standards for lithium iron phosphate batteries. The lithium iron phosphate material regenerated by this method has good electrochemical properties, with a discharge capacity of 137 mAh / g at 1C and a capacity retention rate of 88% after 400 charge and discharge cycles, showing excellent rate performance.
[0094] Comparative Example 1
[0095] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0096] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0097] S3. 0 mg of lithium acetylacetonate was dissolved in a mixed solution of deionized water and ethanol in a volume ratio of 1:1 (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60 ° C for 6 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0098] S4. The spent lithium iron phosphate cathode material treated three times was mixed with 0% glucose and ball-milled for 2 h at a ball-milling speed of 160 rpm, and then calcined at 600° C. for 6 h in an argon atmosphere to obtain the final treated lithium iron phosphate cathode material.
[0099] The difference between Comparative Example 1 and Example 1 is that no lithium salt is added in step S3, and no carbon source material is added for ball milling in step S4. The capacity and cycle performance of the lithium iron phosphate positive electrode material obtained in this comparative example are significantly lower than those in Example 1, and do not meet the national standards for lithium iron phosphate batteries. Figure 7 , Figure 8 As shown, the lithium iron phosphate material finally obtained after treatment by this method has poor electrochemical performance, with a discharge capacity of 124 mAh / g at 1C, and the charge and discharge cycle cannot be maintained after 250 cycles.
[0100] Comparative Example 2
[0101] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0102] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0103] S3. 8 mg (5% wt) of lithium acetylacetonate was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60° C. for 6 h to obtain the third-treated spent lithium iron phosphate cathode material;
[0104] S4. The spent lithium iron phosphate cathode material treated three times was ball-milled for 2 h at a ball-milling speed of 160 rpm, and then calcined at 600 °C for 6 h in an argon atmosphere to obtain a directly regenerated lithium iron phosphate cathode material.
[0105] The difference between Comparative Example 2 and Example 1 is that no carbon source material is added for ball milling in step S4. The capacity and cycle performance of the regenerated lithium iron phosphate positive electrode material in this comparative example are significantly lower than those in Example 1, and do not meet the national standards for lithium iron phosphate batteries. The lithium iron phosphate material regenerated by this method has poor electrochemical performance, with a discharge capacity of 128 mAh / g at 1C and a capacity retention rate of 45% after 400 charge and discharge cycles.
[0106] Comparative Example 3
[0107] S1. The spent lithium iron phosphate cathode material was immersed in deionized water and stirred for 6 hours, and then filtered, and the filtrate was washed with ethanol and dried in a vacuum drying oven at 80°C to obtain a preliminarily treated spent lithium iron phosphate cathode material;
[0108] S2. The failed lithium iron phosphate cathode material subjected to the preliminary treatment was calcined at a temperature of 350° C. for 0.5 h to obtain a secondary treated failed lithium iron phosphate cathode material;
[0109] S3. 8 mg (5% wt in the water-alcohol mixed solution) of lithium hydroxide was dissolved in a mixed solution of deionized water and ethanol (volume ratio 1:1), and then 160 mg of the second-treated spent lithium iron phosphate cathode material powder was added to the mixed solution, magnetically stirred at room temperature for 10 h, filtered and dried in a vacuum drying oven at 60° C. for 6 h to obtain the thrice-treated spent lithium iron phosphate cathode material;
[0110] S4. The spent lithium iron phosphate positive electrode material treated three times was mixed with glucose (the added amount was 7% wt of the spent lithium iron phosphate positive electrode material) and ball-milled for 2 hours at a ball-milling speed of 160 rpm, and then calcined at 600°C for 6 hours in an argon atmosphere to obtain a directly regenerated lithium iron phosphate positive electrode material.
[0111] The difference between Comparative Example 3 and Example 1 is that the lithium salt used in step S3 is lithium hydroxide. Since lithium hydroxide cannot undergo coupling reaction with the surface of black powder, the capacity and cycle performance of the regenerated lithium iron phosphate positive electrode material in this comparative example are significantly lower than those in Example 1, and do not meet the national standards for lithium iron phosphate batteries. The lithium iron phosphate material regenerated by this method has poor electrochemical performance, with a discharge capacity of 126 mAh / g at 1C and a capacity retention rate of 50% after 400 charge and discharge cycles.
[0112] The direct regeneration process of the failed lithium iron phosphate positive electrode material of Examples 1-7 of the present invention is to achieve coupling and impurity removal at room temperature and pressure, reconstruct the lithium replenishment channel, and then efficiently and directly regenerate and repair the failed lithium iron phosphate at high temperature for a short time through multi-step special treatment of the failed positive electrode material, and at the same time add a specific lithium salt to react with an organic solvent in step S3, and then efficiently and directly regenerate and repair the failed lithium iron phosphate at high temperature for a short time, and the regenerated lithium iron phosphate positive electrode material can reach a level comparable to the product performance of normal commercial lithium iron phosphate positive electrode materials, with excellent capacity and cycle performance, in line with the national standards of lithium iron phosphate batteries, and showing excellent rate performance, and because the regeneration process is simple and has little pollution, it can be suitable for large-scale industrial applications. Therefore, the direct regeneration process of the failed lithium iron phosphate positive electrode material of the present invention has obvious advantages over the comparative example, and can effectively meet the high standard requirements of customers and the market.
[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for directly regenerating spent lithium iron phosphate cathode material, characterized in that: The steps include: S1. The spent lithium iron phosphate cathode material is immersed in deionized water and stirred, followed by filtration, and the filtrate is washed with an organic solvent and dried to obtain a preliminarily treated spent lithium iron phosphate cathode material; S2. calcining the initially treated spent lithium iron phosphate cathode material to obtain a secondary treated spent lithium iron phosphate cathode material; S3. The failed lithium iron phosphate cathode material powder after the secondary treatment is added to a mixed solution of deionized water and an alcohol solvent containing a lithium salt, stirred, filtered and then dried to obtain a failed lithium iron phosphate cathode material after the tertiary treatment; S4. The spent lithium iron phosphate positive electrode material treated three times is mixed with a carbon source material and ball-milled, and then calcined to obtain a directly regenerated lithium iron phosphate positive electrode material.
2. The direct regeneration process according to claim 1, characterized in that: The lithium salt in step S3 is one or more of lithium acetylacetonate, lithium acetylacetate, and lithium iodide.
3. The direct regeneration process according to claim 1, characterized in that: The amount of the carbon source material added in step S4 is 5-16% of the mass of the spent lithium iron phosphate positive electrode material.
4. The direct regeneration process according to claim 1, characterized in that: In step S2, the calcination temperature is 250-450° C., and the calcination time is 0.5-2 h.
5. The direct regeneration process according to claim 1, characterized in that: In step S4, the ball milling time is 0.5-5h, and the ball milling speed is 50-220r / min.
6. The direct regeneration process according to claim 1, characterized in that: In step S4, the carbon source material is one or more of cellulose, sucrose, tannic acid, glucose, and vitamin C.
7. The direct regeneration process according to claim 1, characterized in that: In step S4, the calcination temperature is 500-700° C., and the calcination time is 2-6 hours.
8. The direct regeneration process according to claim 1, characterized in that: The concentration of the mixed solution containing lithium salt in step S3 is 3-10wt%.
9. Application of the direct regeneration process according to any one of claims 1 to 8 in treating waste power lithium-ion batteries.
10. Lithium iron phosphate positive electrode material regenerated by the direct regeneration process according to any one of claims 1 to 8.
Citation Information
Patent Citations
Recycling treatment method of waste and old lithium iron phosphate battery anode materials
CN102208706A
Method for recycling lithium iron phosphate wastes in manufacturing link of lithium iron phosphate batteries
CN104362408A
Regeneration method of lithium iron phosphate positive electrode material, lithium iron phosphate positive electrode material and application
CN114744192A
Repair method of lithium iron phosphate positive electrode material, positive electrode material and application
CN115417396A
Method for repairing lithium-deficient lithium iron phosphate pole piece
CN116683078A
